Comparative study of carbon and nitrogen metabolism in spring herbaceous plants along elevation gradient in temperate deciduous forests - Liben Pan; Yuqi Xin; Tianqi Wang; Vladimir L. Gavrikov; Xiaorui Guo; Liqiang Mu; Zhonghua Tang (Journal of Plant Interactions)
Spring herbaceous plants in temperate deciduous forests play a crucial role in promoting nutrient cycling in spring ecosystems. This study examines carbon and nitrogen metabolism differences between two coexisting types of spring herbaceous plants (four early spring plant and four summer green plants) across an elevation gradient. The PCA results indicate that carbon and nitrogen metabolism exhibit strong plant type variation, while elevation variation is relatively low. SE (early spring plants) prioritize above-ground growth and reproduction, enhancing carbon and nitrogen metabolism. Conversely, SG (summer green plants) adopt a shade-tolerant strategy, storing starch in roots for energy in low-light conditions. Both plant types enhance defense by boosting nitrogen metabolism in source organs and accumulating carbon in sink organs. This study provides significant insights into the adaptation strategies of spring herbaceous plants in temperate deciduous forests, highlighting their ecological importance and the metabolic trade-offs between growth and tolerance.